2019
DOI: 10.1186/s12913-018-3855-6
|View full text |Cite
|
Sign up to set email alerts
|

Community-based interventions to enhance healthy aging in disadvantaged areas: perceptions of older adults and health care professionals

Abstract: BackgroundThe number of older adults with different ethnic and socioeconomic background is steadily increasing. There is a need for community-based health promotion interventions for older adults that are responsive to ethnic and socioeconomic diversity among target populations. The aim of this study is to explore encounters between older adults living in disadvantaged areas and health care professionals in the context of community-based health promotion.MethodsQualitative methods were used involving interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…However, engagement in the intervention was challenged by barriers related to cultural and language diversity among residents, together with competing contextual factors (demolition plans, and territorial stigmatization), resulting in doubtful engagement in future interventions. These findings correspond with other studies [9,15] which emphasize a need for context-specific and participatory approaches to ensure that engagement in community-based health promotion interventions in areas of deprivation can be maintained.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, engagement in the intervention was challenged by barriers related to cultural and language diversity among residents, together with competing contextual factors (demolition plans, and territorial stigmatization), resulting in doubtful engagement in future interventions. These findings correspond with other studies [9,15] which emphasize a need for context-specific and participatory approaches to ensure that engagement in community-based health promotion interventions in areas of deprivation can be maintained.…”
Section: Discussionsupporting
confidence: 90%
“…Challenges related to the acceptance of and engagement in health promotion interventions among residents in deprived areas of social housing have previously been identified [9,15]. Nevertheless, our study shows a general positive acceptance of and engagement in community-based interventions among residents living in a deprived area of social housing.…”
Section: Social Relations and Community Engagement As Motives And Persupporting
confidence: 49%
See 2 more Smart Citations
“…A study conducted in Denmark showed that there was a gap between users and providers perception about health promotion services. (5) By lling these gaps, public health programs and community interventions would be conducted more effectively.…”
mentioning
confidence: 99%